The sleeping kidney: microRNA expression profiling of kidney tissue during daily torpor in mice - Panyi Yang; Saif Rehman; Jing Zhang; Ziyin Wang; Zihan Zhao; Bofang Zhang; Kenneth B. Storey; Yuhong Hu; Hui Wang (Functional & Integrative Genomics, 2026)

Dynamic regulation of histone arginine methylation in anoxic freshwater turtles - Tighe Bloskie; Kenneth B. Storey (Journal of Comparative Physiology B, 2026)

Phylogenomics insights into the evolution of pronotal leaf mimicry in Hierodulinae (Mantodea: Mantidae) - Xiao-Dong Xu; Chen-Yang Shen; Kenneth B. Storey; Dan-Na Yu; Yue Ma; Jia-Yong Zhang (Molecular Phylogenetics and Evolution, 2026)

Molecular mechanisms underlying population-specific thermal stress responses in the rice-paddy frog (Fejervarya multistriata) - Xiao-Dong Xu; Ling-Na Cai; Kenneth B. Storey; Jia-Yong Zhang; Dan-Na Yu (Journal of Thermal Biology, 2025)

Alpha-ketoglutarate supplementation differently modifies hematological parameters and oxidative stress in mice fed a standard diet and high-fat high-fructose diet - Myroslava V. Vatashchuk; Viktoriia V. Hurza; Oleksandra B. Abrat; Maria P. Lylyk; Khrystyna Matvieieva; Dmytro V. Gospodaryov; Oleh I. Demianchuk; Kenneth B. Storey; Maria M. Bayliak; Volodymyr I. Lushchak (Journal of Physiology and Biochemistry, 2025)

Levels of post-translationally modified histones in ground squirrel livers are altered during deep torpor - Remy Carter; Kenneth B. Storey (Cryobiology, 2025)

The role of microRNA in the regulation of hepatic metabolism and energy-expensive processes in the hibernating dormouse - W. Aline Ingelson-Filpula; Anna Kübber-Heiss; Johanna Painer; Gabrielle Stalder; Hanane Hadj-Moussa; Fabrice Bertile; Caroline Habold; Sylvain Giroud; Kenneth B. Storey (Cryobiology, 2025)

Histone Modifications in the Anoxic Northern Crayfish, Faxonius virilis - Imane Rhzali; Kenneth B. Storey (Marine Biotechnology, 2025)

Dynamics of epigenetic regulation in Dryophytes versicolor skeletal muscle: Lysine methylation and acetylation involvement in metabolic rate depression - Saif Rehman; Kenneth B. Storey (Journal of Thermal Biology, 2024)

A potential feeding regulation strategy during aestivation: Relaxation of intestine mediated by pedal peptide/orcokinin-type neuropeptides in sea cucumber Apostichopus japonicus - Yingqiu Zheng; Huachen Liu; Xiao Cong; Kenneth B. Storey; Muyan Chen (Aquaculture, 2024)

The effects of nickel chloride on papillary muscle contractility under normothermic and hypothermic conditions: Comparison of active and hibernating ground squirrels (Urocitellus undulatus) with Wistar rats. - Alexey S. Averin; Kenneth B. Storey; Miroslav N. Nenov (Journal of Thermal Biology, 2024)

Microrna regulation of hepatic metabolism and energy-expensive processes during torpor in the garden dormouse - W. Aline Ingelson-Filpula; Sylvain Giroud; Kenneth B. Storey (Cryobiology, 2023)

Sub-zero microrna expression in the liver of frozen Chrysemys picta marginata - Anchal Varma; Sarah A. Breedon; Kenneth B. Storey (Cryobiology, 2023)

Differential bone remodeling mechanism in hindlimb unloaded and hibernating Daurian ground squirrels: a comparison between artificial and natural disuse within the same species - Xuli Gao; Siqi Wang; Siqi Shen; Shuyao Wang; Manjiang Xie; Kenneth B. Storey; Caiyong Yu; Etienne Lefai; Wenqian Song; Hui Chang; Changbin Yang (Journal of Comparative Physiology B, 2023)

Characterization and expression profile of transient receptor potential channels in sea cucumber Apostichopus japonicus - Xuemin Wang; Yixin Wang; Yanlin Wang; Kenneth B. Storey; Muyan Chen (Frontiers in Marine Science, 2023)
Background In the past few decades, heat waves and seasonal variation linked with global warming are causing frequent fluctuations of water temperature in aquatic environments, resulting in further challenges for marine organisms. As a poikilothermic marine animal and a temperate species, sea cucumber A. japonicus is also very sensitive to temperature variation and shows a limited ability to adapt to environmental temperature changes. However, the molecular mechanisms by which A. japonicus perceives signals from such a diverse environment including the trigger of aestivation still remain unclear. TRP (transient receptor potential) superfamily, as the great potential “sentinel” of the organism in response to the changes of the external environment signals, perceived little attention and will be the future great candidates for sensory function research in echinoderm. Methods BLAST program was applied to identify the AjTRPs based on A. japonicus transcriptome database. Gene structure analysis of AjTRPs and phylogenetic analysis of TRPs were performed. The expression profiles of AjTRPs in different tissues and in response to different heat stress treatments (chronic/ acute) were measured using qRT-PCR. Results A total of 54 TRPs were identified in A. japonicus . Gene structure analysis showed that the exon numbers and the domains of AjTRPs varied greatly. Phylogenetic analysis indicated that AjTPRs were mainly grouped into six subfamilies: TRPA, TRPM, TRPC, TRPV, TRPML, and TRPP. Copy numbers of each TRP member in marine invertebrates including A. japonicus were more than those in vertebrates, however some TRP channel members were lost in invertebrates. Expression profile detection suggested that the representative 15 AjTRP genes belonging to 6 subfamilies were expressed in all tissues examined. Conclusion Our findings indicate that the plastic evolutionary history of TRP channel genes and suggest that TRPM2-1, TRPM2-2, TRPM3, and TRPC3-1 are potential thermo-TRP proteins involved in thermal regulation in A. japonicus . This work facilitates the knowledge of TRP-mediated sensory systems in echinoderms, provides new insights into the mechanisms of aestivation and global warming adaptation in marine invertebrates.

Role of FOXO transcription factors in the tolerance of whole-body freezing in the wood frog, Rana sylvatica - Saif Rehman; Hanane Hadj-Moussa; Liam Hawkins; Kenneth B Storey (Cryobiology, 2023)

Hypoxia inducible factor-1α responds to freezing, anoxia and dehydration stresses in a freeze-tolerant frog - Janet M. Storey; Zhenhong Li; Kenneth B. Storey (Cryobiology, 2023)

Purification and characterization of NADP-isocitrate dehydrogenase from skeletal muscle of Urocitellus richardsonii - Isabelle A. MacLean; Anchal Varma; Kenneth B. Storey (Molecular and Cellular Biochemistry, 2023)

Sub-zero microRNA expression in the liver of the frozen hatchling painted turtle, Chrysemys picta marginata - Anchal Varma; Sarah A. Breedon; Kenneth B. Storey (Science of The Total Environment, 2023)

Differential bone metabolism and protein expression in mice fed a high-fat diet versus Daurian ground squirrels following natural pre-hibernation fattening - Xuli Gao; Shenyang Shen; Qiaohua Niu; Weilan Miao; Yuting Han; Ziwei Hao; Ning An; Yingyu Yang; Yu Zhang; Han Zhang; Kenneth B. Storey; Hui Chang (Journal of Zhejiang University-SCIENCE B, 2022)

High stability of blood parameters during mouse lifespan: sex-specific effects of every-other-day fasting - Maria M. Bayliak; Oksana M. Sorochynska; Oksana V. Kuzniak; Ivanna Z. Drohomyretska; Andriy Ya. Klonovskyi; Anastasia O. Hrushchenko; Myroslava V. Vatashchuk; Nadia M. Mosiichuk; Kenneth B. Storey; Olga Garaschuk; Volodymyr I. Lushchak (Biogerontology, 2022)

MicroRNA biogenesis proteins follow tissue-dependent expression during freezing in Dryophytes versicolor - W. Aline Ingelson-Filpula; Kenneth B. Storey (Journal of Comparative Physiology B, 2022)

Regulation of Apoptosis and Autophagy During Anoxia in the Freshwater Crayfish, Faxonius virilis - Sarah A. Breedon; Aakriti Gupta; Kenneth B. Storey (Marine Biotechnology, 2022)

PacBio Isoform Sequencing and Illumina RNA Sequencing Provide Novel Insights on Responses to Acute Heat Stress in Apostichopus japonicus Coelomocytes - Yanlin Wang; Yingchao Yin; Xiao Cong; Kenneth B. Storey; Muyan Chen (Frontiers in Marine Science, 2022)
Significant increases in global sea surface temperatures are expected with climate change and may cause a serious challenge for marine organisms cultured in aquatic environments that are characterized by short and long-term fluctuations in water temperatures. Apostichopus japonicus , a sea cucumber with high nutritional value and pharmacological properties, is an important economic species that is widely raised in aquaculture in China. In recent years, continuous extreme high temperatures (up to 30°C) have occurred frequently in summer leading to mass mortality of sea cucumbers cultured in semi-open shallow regions seriously restricting the sustainable development of sea cucumber aquaculture. In the present study, we combined RNA-seq and PacBio single-molecular real-time (SMRT) sequencing technology to unveil the potential mechanisms of response to acute heat stress in A. japonicus coelomocytes. A total of 1,375 differentially expressed genes (DEGs) were identified in a comparison of control and 48 h heat stress (HS) groups. Pathway enrichment analysis indicated that nine important pathways induced by HS were significantly enriched ( q -value < 0.05) and mostly fell into four classes: folding, sorting, and degradation, immune and infectious diseases, signal transduction, and post-transcriptional regulation. Among them, all 41 genes connected with protein processing in endoplasmic reticulum were significantly up-regulated, and 12 of these were selected and validated via qPCR. Furthermore, changes in alternative splicing (AS) were also identified in sea cucumbers following HS. A total of 1,224 and 1,251 differential alternative splicing (DAS) events were identified using splice junction counts (JC only) and reads on target and junction counts (JCEC) as the input for rMATS in CO-HS comparison. We further found that the RNA splicing-related genes were enriched in the spliceosome pathway and showed DAS in control versus heat-stressed animals. In particular, we compared and confirmed that the hsfs1 gene, the master regulator of the heat shock response, showed differentially spliced exons in response to HS. This is the first comprehensive study showing that transcriptional and post-transcriptional (AS) controls are involved in the acute heat stress response of sea cucumber coelomocytes and provides novel insights into the molecular mechanisms of echinoderm adaptation to environmental stress.

Epigenetic regulation by DNA methyltransferases during torpor in the thirteen-lined ground squirrel Ictidomys tridecemlineatus - Shannon N. Tessier; W. Aline Ingelson-Filpula; Kenneth B. Storey (Molecular and Cellular Biochemistry, 2021)

Insights from a vertebrate model organism on the molecular mechanisms of whole-body dehydration tolerance - Bryan E. Luu; Liam J. Hawkins; Kenneth B. Storey (Molecular and Cellular Biochemistry, 2021)

Middle aged turn point in parameters of oxidative stress and glucose catabolism in mouse cerebellum during lifespan: minor effects of every-other-day fasting - Maria M. Bayliak; Nadia M. Mosiichuk; Oksana M. Sorochynska; Oksana V. Kuzniak; Lesia O. Sishchuk; Anastasiia O. Hrushchenko; Alina O. Semchuk; Taras V. Pryimak; Yulia V. Vasylyk; Dmytro V. Gospodaryov; Kenneth B. Storey; Olga Garaschuk; et al. (Biogerontology, 2021)

Every-other-day fasting reduces glycolytic capability in the skeletal muscle of young mice - Oksana M. Sorochynska; Oksana V. Kuzniak; Maria M. Bayliak; Yulia V. Vasylyk; Kenneth B. Storey; Volodymyr I. Lushchak (Biologia, 2021)

Ultrastructural variation and key ER chaperones response induced by heat stress in intestinal cells of sea cucumber Apostichopus japonicus - Shasha Wang; Yingqiu Zheng; Muyan Chen; Kenneth B. Storey (Journal of Oceanology and Limnology, 2021)

Freeze tolerance and the underlying metabolite responses in the Xizang plateau frog, Nanorana parkeri - Yonggang Niu; Wangjie Cao; Jinzhou Wang; Jie He; Kenneth B. Storey; Li Ding; Xiaolong Tang; Qiang Chen (Journal of Comparative Physiology B, 2021)

Dynamic regulation of histone H3 lysine (K) acetylation and deacetylation during prolonged oxygen deprivation in a champion anaerobe - Sanoji Wijenayake; Kenneth B. Storey (Molecular and Cellular Biochemistry, 2020)

MondoA:MLX complex regulates glucose-dependent gene expression and links to circadian rhythm in liver and brain of the freeze-tolerant wood frog, Rana sylvatica - Gurjit Singh; Kenneth B. Storey (Molecular and Cellular Biochemistry, 2020)

Development of fly tolerance to consuming a high-protein diet requires physiological, metabolic and transcriptional changes - Ihor S. Yurkevych; Lindsey J. Gray; Dmytro V. Gospodaryov; Nadia I. Burdylyuk; Kenneth B. Storey; Stephen J. Simpson; Oleh Lushchak (Biogerontology, 2020)

Metabolic characteristics of overwintering by the high-altitude dwelling Xizang plateau frog, Nanorana parkeri - Yonggang Niu; Wangjie Cao; Kenneth B. Storey; Jie He; Jinzhou Wang; Tao Zhang; Xiaolong Tang; Qiang Chen (Journal of Comparative Physiology B, 2020)

Nanodelivery of phytobioactive compounds for treating aging-associated disorders - Oleh Lushchak; Olha Strilbytska; Alexander Koliada; Alina Zayachkivska; Nadia Burdyliuk; Ihor Yurkevych; Kenneth B. Storey; Alexander Vaiserman (GeroScience, 2020)

Purification of carbamoyl phosphate synthetase 1 (CPS1) from wood frog (Rana sylvatica) liver and its regulation in response to ice-nucleation and subsequent whole-body freezing - Stuart R. Green; Kenneth B. Storey (Molecular and Cellular Biochemistry, 2019)

Purification and characterization of a urea sensitive lactate dehydrogenase from skeletal muscle of the African clawed frog, Xenopus laevis - Christine L. Childers; Kenneth B. Storey (Journal of Comparative Physiology B, 2019)

Metformin as a geroprotector: experimental and clinical evidence - Veronika Piskovatska; Nadiya Stefanyshyn; Kenneth B. Storey; Alexander M. Vaiserman; Oleh Lushchak (Biogerontology, 2019)

A functional transcriptomic analysis in the relict marsupial Dromiciops gliroides reveals adaptive regulation of protective functions during hibernation - Roberto F. Nespolo; Juan Diego Gaitan‐Espitia; Julian F. Quintero‐Galvis; Fernanda V. Fernandez; Andrea X. Silva; Cristian Molina; Kenneth B. Storey; Francisco Bozinovic (Molecular Ecology, 2018)
The small South American marsupial, Dromiciops gliroides , known as the missing link between the American and the Australian marsupials, is one of the few South American mammals known to hibernate. Expressing both daily torpor and seasonal hibernation, this species may provide crucial information about the mechanisms and the evolutionary origins of marsupial hibernation. Here, we compared torpid and active individuals, applying high‐throughput sequencing technologies ( RNA ‐seq) to profile gene expression in three D. gliroides tissues and determine whether hibernation induces tissue‐specific differential gene expression. We found 566 transcripts that were significantly up‐regulated during hibernation (369 in brain, 147 in liver and 50 in skeletal muscle) and 339 that were down‐regulated (225 in brain, 79 in liver and 35 in muscle). The proteins encoded by these differentially expressed genes orchestrate multiple metabolic changes during hibernation, such as inhibition of angiogenesis, prevention of muscle disuse atrophy, fuel switch from carbohydrate to lipid metabolism, protection against reactive oxygen species and repair of damaged DNA . According to the global enrichment analysis, brain cells seem to differentially regulate a complex array of biological functions (e.g., cold sensitivity, circadian perception, stress response), whereas liver and muscle cells prioritize fuel switch and heat production for rewarming. Interestingly, transcripts of thioredoxin‐interacting protein ( TXNIP ), a potent antioxidant, were significantly over‐expressed during torpor in all three tissues. These results suggest that marsupial hibernation is a controlled process where selected metabolic pathways show adaptive modulation that can help to maintain homeostasis and enhance cytoprotection in the hypometabolic state.

Regulation of nuclear factor of activated T cells (NFAT) and downstream myogenic proteins during dehydration in the African clawed frog - Yichi Zhang; Simon G. English; Kenneth B. Storey (Molecular Biology Reports, 2018)

Translational regulation in the anoxic turtle, Trachemys scripta elegans - Kama E. Szereszewski; Kenneth B. Storey (Molecular and Cellular Biochemistry, 2018)

Acute exposure to copper induces variable intensity of oxidative stress in goldfish tissues - Viktor V. Husak; Nadia M. Mosiichuk; Olga I. Kubrak; Tetiana M. Matviishyn; Janet M. Storey; Kenneth B. Storey; Volodymyr I. Lushchak (Fish Physiology and Biochemistry, 2018)

Purification and characterization of skeletal muscle pyruvate kinase from the hibernating ground squirrel, Urocitellus richardsonii: potential regulation by posttranslational modification during torpor - Ryan A. V. Bell; Kenneth B. Storey (Molecular and Cellular Biochemistry, 2018)

Regulation of Smad mediated microRNA transcriptional response in ground squirrels during hibernation - Cheng-Wei Wu; Kenneth B. Storey (Molecular and Cellular Biochemistry, 2018)

Dietary l-arginine accelerates pupation and promotes high protein levels but induces oxidative stress and reduces fecundity and life span in Drosophila melanogaster - Maria M. Bayliak; Maria P. Lylyk; Oksana V. Maniukh; Janet M. Storey; Kenneth B. Storey; Volodymyr I. Lushchak (Journal of Comparative Physiology B, 2018)

Histone methylation in the freeze-tolerant wood frog (Rana sylvatica) - Liam J. Hawkins; Kenneth B. Storey (Journal of Comparative Physiology B, 2018)

Turn down genes for WAT? Activation of anti-apoptosis pathways protects white adipose tissue in metabolically depressed thirteen-lined ground squirrels - Samantha M. Logan; Bryan E. Luu; Kenneth B. Storey (Molecular and Cellular Biochemistry, 2016)

The role of DNA methylation during anoxia tolerance in a freshwater turtle (Trachemys scripta elegans) - Sanoji Wijenayake; Kenneth B. Storey (Journal of Comparative Physiology B, 2016)

Response of the JAK-STAT pathway to mammalian hibernation in 13-lined ground squirrel striated muscle - Samantha M. Logan; Shannon N. Tessier; Joann Tye; Kenneth B. Storey (Molecular and Cellular Biochemistry, 2016)

MicroRNA regulation in heart and skeletal muscle over the freeze–thaw cycle in the freeze tolerant wood frog - Saumya Bansal; Bryan E. Luu; Kenneth B. Storey (Journal of Comparative Physiology B, 2016)

Expression of nuclear factor of activated T cells (NFAT) and downstream muscle-specific proteins in ground squirrel skeletal and heart muscle during hibernation - Yichi Zhang; Kenneth B. Storey (Molecular and Cellular Biochemistry, 2016)

Identification and profiling of miRNAs in the freeze-avoiding gall moth Epiblema scudderiana via next-generation sequencing - Pierre J. Lyons; Nicolas Crapoulet; Kenneth B. Storey; Pier Jr Morin (Molecular and Cellular Biochemistry, 2015)

Characterization of adipocyte stress response pathways during hibernation in thirteen-lined ground squirrels - Andrew N. Rouble; Shannon N. Tessier; Kenneth B. Storey (Molecular and Cellular Biochemistry, 2014)

Purification and characterization of a urea sensitive lactate dehydrogenase from the liver of the African clawed frog, Xenopus laevis - Barbara A. Katzenback; Neal J. Dawson; Kenneth B. Storey (Journal of Comparative Physiology B, 2014)

FoxO3a-mediated activation of stress responsive genes during early torpor in a mammalian hibernator - Cheng-Wei Wu; Kenneth B. Storey (Molecular and Cellular Biochemistry, 2014)

Oxidative stress as a mechanism for toxicity of 2,4-dichlorophenoxyacetic acid (2,4-D): studies with goldfish gills - Tetiana M. Atamaniuk; Olga I. Kubrak; Kenneth B. Storey; Volodymyr I. Lushchak (Ecotoxicology, 2013)

Activation of the unfolded protein response during anoxia exposure in the turtle Trachemys scripta elegans - Anastasia Krivoruchko; Kenneth B. Storey (Molecular and Cellular Biochemistry, 2013)

HIF-1α regulation in mammalian hibernators: role of non-coding RNA in HIF-1α control during torpor in ground squirrels and bats - Yulia Maistrovski; Kyle K. Biggar; Kenneth B. Storey (Journal of Comparative Physiology B, 2012)

An enzymatic bridge between carbohydrate and amino acid metabolism: regulation of glutamate dehydrogenase by reversible phosphorylation in a severe hypoxia-tolerant crayfish - Neal J. Dawson; Kenneth B. Storey (Journal of Comparative Physiology B, 2012)

Regulation of tail muscle arginine kinase by reversible phosphorylation in an anoxia-tolerant crayfish - Neal J. Dawson; Kenneth B. Storey (Journal of Comparative Physiology B, 2011)

Expression of myocyte enhancer factor-2 and downstream genes in ground squirrel skeletal muscle during hibernation - Shannon N. Tessier; Kenneth B. Storey (Molecular and Cellular Biochemistry, 2010)

Regulation of glucose-6-phosphate dehydrogenase by reversible phosphorylation in liver of a freeze tolerant frog - Christopher A. Dieni; Kenneth B. Storey (Journal of Comparative Physiology B, 2010)

Epigenetics in anoxia tolerance: a role for histone deacetylases - Anastasia Krivoruchko; Kenneth B. Storey (Molecular and Cellular Biochemistry, 2010)

Regulation of the heat shock response under anoxia in the turtle, Trachemys scripta elegans - Anastasia Krivoruchko; Kenneth B. Storey (Journal of Comparative Physiology B, 2010)

The regulation of AMPK signaling in a natural state of profound metabolic rate depression - Christopher J. Ramnanan; David C. McMullen; Amy G. Groom; Kenneth B. Storey (Molecular and Cellular Biochemistry, 2010)

Phosphorylation of translation factors in response to anoxia in turtles, Trachemys scripta elegans: role of the AMP-activated protein kinase and target of rapamycin signalling pathways - Mark H. Rider; Nusrat Hussain; Stephen M. Dilworth; Kenneth B. Storey (Molecular and Cellular Biochemistry, 2009)

AMP-deaminase from goldfish white muscle: regulatory properties and redistribution under exposure to high environmental oxygen level - Volodymyr I. Lushchak; Viktor V. Husak; Janet M. Storey; Kenneth B. Storey (Fish Physiology and Biochemistry, 2009)

Regulation of global protein translation and protein degradation in aerobic dormancy - Christopher J. Ramnanan; Marcus E. Allan; Amy G. Groom; Kenneth B. Storey (Molecular and Cellular Biochemistry, 2009)

Skeletal muscle hexokinase: regulation in mammalian hibernation - Khalil Abnous; Kenneth B. Storey (Molecular and Cellular Biochemistry, 2008)

Expression of Nrf2 and its downstream gene targets in hibernating 13-lined ground squirrels, Spermophilus tridecemlineatus - Pier Jr Morin; Zhouli Ni; David C. McMullen; Kenneth B. Storey (Molecular and Cellular Biochemistry, 2008)

The regulation of thapsigargin-sensitive sarcoendoplasmic reticulum Ca2+-ATPase activity in estivation - Christopher J. Ramnanan; Kenneth B. Storey (Journal of Comparative Physiology B, 2008)

Freezing and anoxia tolerance of slugs: a metabolic perspective - Kenneth B. Storey; Janet M. Storey; Thomas A. Churchill (Journal of Comparative Physiology B, 2007)

Arrest of transcription following anoxic exposure in a marine mollusc - Kevin Larade; Kenneth B. Storey (Molecular and Cellular Biochemistry, 2007)

Purification and properties of glutathione reductase from liver of the anoxia-tolerant turtle, Trachemys scripta elegans - William. G. Willmore; Kenneth. B. Storey (Molecular and Cellular Biochemistry, 2007)

Up-regulation of the endoplasmic reticulum molecular chaperone GRP78 during hibernation in thirteen-lined ground squirrels - Hapsatou Mamady; Kenneth B. Storey (Molecular and Cellular Biochemistry, 2006)

HIF-1α involvement in low temperature and anoxia survival by a freeze tolerant insect - Pier Morin; David C. McMullen; Kenneth B. Storey (Molecular and Cellular Biochemistry, 2005)

Effects of hibernation on multicatalytic proteinase complex in thirteen-lined ground squirrels, Spermophilus tridecemlineatus - Ashley K. Woods; Kenneth B. Storey (Molecular and Cellular Biochemistry, 2005)

Cloning and expression of PPARγ and PGC-1α from the hibernating ground squirrel, Spermophilus tridecemlineatus - Sean F. Eddy; Pier Morin; Kenneth B. Storey (Molecular and Cellular Biochemistry, 2005)

Reversible suppression of protein synthesis in concert with polysome disaggregation during anoxia exposure in Littorina littorea - Kevin Larade; Kenneth B. Storey (Molecular and Cellular Biochemistry, 2002)

Reassessment of the cold‐labile nature of phosphofructokinase from a hibernating ground squirrel - Justin A. MacDonald; Kenneth B. Storey (Molecular and Cellular Biochemistry, 2001)

Activation of mitogen-activated protein kinases during natural freezing and thawing in the wood frog - Steven C. Greenway; Kenneth B. Storey (Molecular and Cellular Biochemistry, 2000)

Reversible phosphorylation control of skeletal muscle pyruvate kinase and phosphofructokinase during estivation in the spadefoot toad, Scaphiopus couchii - Kyra J. Cowan; Kenneth B. Storey (Molecular and Cellular Biochemistry, 1999)

Role of antioxidant defenses in the tolerance of severe dehydration by anurans. The case of the leopard frog Rana pipiens - Marcelo Hermes-Lima; Kenneth B. Storey (Molecular and Cellular Biochemistry, 1998)

Second messenger and cAMP-dependent protein kinase responses to dehydration and anoxia stresses in frogs - Clark P. Holden; Kenneth B. Storey (Journal of Comparative Physiology B, 1997)